KATA SAPAAN NON-KEKERABATAN MASYARAKAT BUGIS BONE DI DESA SUNGAI RAYA KECAMATAN NIPAH PANJANG KABUPATEN TANJUNG JABUNG TIMUR (KAJIAN SOSIOPRAGMATIK) - Ade Rahima; Ike Novita (Universitas Batanghari, 2021)
This study examines the non-kinship greetings of Bugis Bone society in Sungai Raya Village, Nipah Panjang Subdistrict, Tanjung Jabung Timur Regency. This study uses the qualitative descriptive method. This study's data is in the form of oral utterances about non-kinship greetings used to greet and give greetings in daily communication in Sungai Raya Village, Nipah Panjang District, Tanjung Jabung Timur Regency. The subject of this research is a native in Sungai Raya Village, Nipah Panjang Subdistrict, Tanjung Jabung Timur Regency. Six informants became speakers through data collection techniques with the direction of the wind. At the same time, the data analysis technique is done with sociopragmatic theory. The result of this research is a description of the form of non-kinship greetings of Bugis Bone village Sungai Raya District Nipah Panjang Tanjung Jabung Timur. As for the form of the greeting word, this is a greeting in religion such as Pak Imang ’Imam Masjid’. Furthermore, greetings in customs are Andi which means 'descendants of nobles'. While the word greeting in the general public such as Puang 'unknown elder'.